A voltammetric tool for the evaluation of propolis antioxidant activity - Falcão, Soraia (2018)
Propolis (bee glue) is a sticky dark-colored material that honeybees collected from parts of plants, buds and exudates, and used as construction and defense material in the hive. This resinous substance is a rich source of phenolic compounds, and its chemical composition is strongly influenced by its phytogeographic origin. This research outlines the evaluation of the redox profile and the quantification of the total antioxidant capacity in Portuguese propolis from different origins and potential floral sources Populus x canadensis Moench and Cistus ladanifer L through cyclic voltammetry and differential pulse voltammetry. Although several oxidation processes were showed by propolis samples, which were dependent of the resin origin, common oxidation potentials within the majority of samples of a region were detected, suggesting an analogous chemical composition in respect of electroactive species. Based on the quantification of the total electroactive antioxidant power, it was found that propolis with higher antioxidant activity was from coast center, followed by north ~ Azores Archipelago > central interior > Madeira Island > south.